Biographische Real-Fiktion als Paradigma narrativer Erklärung - Groeben, Norbert (Journal of literary theory, 2020)
The two categories of »fiction« and »non-fiction« are most often conceived of - and treated as - disjointed and separate, not only in common sense but also in literary studies. This does not adequately reflect, however, the developmental trajectory of the non-fiction genre over the course of the twentieth century. After all, the popularization of expert knowledge has increasingly been effected with the help of narrative strategies which raise one crucial question: Just how much fiction can the factual nature - the dependence on facts - of non-fiction tolerate? However, as the more precise definition of the pertinent term, »fiction«, indicates, a distinction must be made between »fictionality«, on the one hand, and »fictivity«, on the other. »Fictionality«, that is to say, refers to narrative strategies analogous to those of fiction , but which relate to historical facts. »Fictivity«, by contrast, refers to the representation of fictitious content .